Systematic out‐of‐field secondary neutron spectrometry and dosimetry in pencil beam scanning proton therapy. Issue 5 (20th April 2017) - Trinkl, Sebastian; Mares, Vladimir; Englbrecht, Franz Siegfried; Wilkens, Jan Jakob; Wielunski, Marek; Parodi, Katia; Rühm, Werner; Hillbrand, Martin
Abstract : Background and purpose: Systematic investigation of the energy and angular dependence of secondary neutron fluence energy distributions and ambient dose equivalents values (H*(10)) inside a pencil beam scanning proton therapy treatment room using a gantry. Materials and methods: Neutron fluence energy distributions were measured with an extended‐range Bonner sphere spectrometer featuring ³He proportional counters, at four positions at 0°, 45°, 90°, and 135° with respect to beam direction and at a distance of 2 m from the isocenter. The energy distribution of secondary neutrons was investigated for initial proton beam energies of 75 MeV, 140 MeV, and 200 MeV, respectively, using a 2D scanned irradiation field of 11 × 11 cm² delivered to a 30 × 30 × 30 cm³ PMMA phantom. Additional measurements were performed at a proton energy of 118 MeV including a 5 cm range‐shifter (PMMA), yielding a Bragg peak position similar to that of 75 MeV protons. Results: Ambient dose equivalent values from 0.3 μSv/Gy (75 MeV; 90°) to 24 μSv/Gy (200 MeV; 0°) were measured inside the treatment room at a distance of 2 m from the isocenter. H*(10) values were lower (by factors of up to 7.2 (at 45°)) at 75 MeV compared to those at 118 MeV with the 5 cm range‐shifter. At 0° and 45°, an evaporation peak was found in the measured neutron fluence energy distributions, at neutron energies around MeV, which contributes about 50% to total H*(10) values, for all investigated proton beam energies. Conclusions: This study showed a pronounced increase of secondary neutron H*(10) values inside the proton treatment room with increasing proton energy without beam modifiers. For example, in beam direction this increase was about a factor of 50 when protons of 75 MeV and 200 MeV were compared. The existence of a peak of secondary neutrons in the MeV region was demonstrated in beam direction (0°). This peak is due to evaporation neutrons produced in the existing surrounding materials such as those used for the gantry. Therefore, any simulation of the secondary neutrons within a proton treatment room must take these materials into account. In addition, the results obtained here show that the use of a range‐shifter increases the production of secondary neutrons inside the treatment room. Using a range‐shifter, the higher neutron doses observed mainly result from the higher incident proton energy (118 MeV instead of 75 MeV when no range‐shifter was used), due to higher neutron production cross‐sections.